Duathlon performance unaltered by short-term changes in dietary fat and carbohydrates - Moncada Jiménez, José (2009)
Purpose: This study investigated the effects of short-term dietary changes on metabolism and duathlon performance. Methods: Eleven men underwent a high-fat (HF; >65% fat from energy) or a high-carbohydrate (CHO; HC) diet (>60% CHO from energy). Energy intake was individualized, and commercially available foods were prepared and packaged for each participant 48 hr before they completed a laboratory-based duathlon (5-km run, 30 km cycling, and 10-km run). Blood samples were obtained before, immediately after, and 1 and 2 hr after the duathlon for determination of glucose, insulin, and glucagon. Oxygen consumption, ratings of perceived exertion (RPE), and respiratory-exchange ratio were assessed, and fat and CHO oxidation were estimated before, during, and after the duathlon. Results: Dietary records indicated a significant difference in fat content ingested before the duathlons (p < .05). Time to complete the duathlon did not differ between the HC- and the HF-diet trials. CHO-oxidation rate was higher during the HC-diet trial than during the HF-diet trial (p = .006). Fat-oxidation rates were higher in the HF-diet trial than in the HC-diet trial (p = .001). No differences in RPE were found between dietary trials. Blood glucose concentration was higher immediately after the duathlon in the HC-diet trial than in the HF-diet trial and remained higher 1 and 2 hr after the duathlon (p < .05). Conclusion: Duathlon performance was not altered by short-term changes in dietary fat or CHO composition despite higher blood glucose concentrations under the HC condition.